Desenvolvimento de procedimentos de digestão de biodiesel assistidos por radiação ultrassônica visando à determinação de metais por técnicas eletroquímicas - Freitas, Helieder Cortes (2015)
This thesis presents the use of ultrasonic radiation for the digestion of biodiesel samples (B100) for the determination of metal ions by electrochemical stripping techniques (potentiometric and voltammetric) using a glassy-carbon electrode modified with a mercury film. Biodiesel samples (50 mg) were subjected to digestion in glass tubes with a mixture of 3.0 mL of concentrated HCl and 4.4 ml H2O2 (30%), placed in an ultrasonic bath (40 kHz and 120 W) exactly on the higher intensity region (piezoelectric) of the ultrasound and sonicated for 40 min at room temperature (~ 20°C). These parameters were optimized using the chemometric technique of factorial design for the analysis of biodiesel samples spiked with ethanolic standard solutions of zinc, cadmium, lead and copper. Recovery values between 97 and 107% were observed in the optimal conditions found to zinc, cadmium, lead and copper. Residual carbon content (RCC) values after digestions were in the range of 3.05 to 3.75%. The simultaneous determination of zinc, cadmium, lead and copper using anodic stripping voltammetry revealed limit of detection (LD) values of 44 ng kg -1; 30 ng kg -1; 145 ng kg -1; 96 ng kg -1, respectively. Additionally, biodiesel samples (100 mg) were also treated in glass tubes with a mixture of 1.59 mL concentrated HCl and 3.0 ml H2O2 (30%) under sonication of an ultrasonic probe (sonication time 12.5 min, 25% amplitude, pulse of 5.0 s and time interval of 2.0 s). The parameters were also optimized employing the chemometric technique of factorial design for the analysis of spiked samples. Recovery values between 95 and 104% were observed in the satisfactory condition for zinc, cadmium, lead and copper. RCC values after digestions comprised values between 0.43 to 0.54%. For the simultaneous determination of zinc, cadmium, lead and copper using anodic stripping voltammetry obtained in the digestates employing the ultrasonic probe, the LD values found respectively for zinc, cadmium and copper were 25 ng kg -1 and for lead 56 ng kg -1. All results obtained using assisted digestion by ultrasonic bath and / or ultrasonic probe indicate that the proposed methods for the biodiesel sample preparation presents a comparable performance to traditional methods of digestion using acid blends, or yet digestions assisted by microwave radiation.